Effective fault localization technique using parameter-value replacement - Xing-ya WANG; Shu-juan JIANG; Xiao-lin JU; He-ling CAO (Tongxin xuebao, 2015)
Statistic-based fault localization and slice-based fault localization cannot locate the omission faults effectively.A method-level fault localization approach based on parameter-value replacement was proposed.Those methods appearing in failed executions were treated as the fault methods candidate set (FMCS).For each element contained in FMCS，its impact to the execution result was measured and then the FMCS elements based on the impact were classified.For each method with high impact，its interesting parameter value mapping pair (IPVMP) was searched by using parameter-value replacement.According to the impact and IPVMP，a method list of FMCS elements was finally provided to debuggers.Empirical results show that the proposed approach performs better than other fault localization approaches.